Analytical and Numerical Solution for H-type Darrieus Wind Turbine Performance at the Tip Speed Ratio of Below One - Ghiasi, Pedram; Najafi, Gholamhassan; Ghobadian, Barat; Jafari, Ali (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
H-type Darrieus vertical axis wind turbines (VAWT) have omnidirectional movement capability and can get more power compared to other VAWTs at high tip speed ratios (ðœ†). However, its disadvantages are self-starting inability and low generated power at ðœ† less than 1. The performance of H-type Darrieus wind turbine at ðœ†<1 was studied using double multiple stream tube (DMST) model and two-dimensional computational fluid dynamic (CFD) simulation. In CFD simulation, the Unsteady Reynolds Averaged Navier-Stokes (URANS) equations were used and the turbulence model was solved with SST k-Ï‰ model. The performance of fifteen various wind turbines was determined at fourteen wind velocities by two solution methods. The effect of chord length, solidity, Reynolds number and Height to Diameter (H/D) ratio were investigated on generated torque, power and the time required to reach ðœ†=0.1. Increasing in the moment of inertia due to the increasing in required time to reach ðœ†=0.1. In the low TSRs, the wind turbines can generate higher torque and power in high Re numbers and solidities. The required time was reduced by an increase in Re number and solidity. Finally, the best ratio of H/D of H-type Darrieus wind turbines was defined to improve the turbine performance.